Density of states and differential entropy in Dirac materials in crossed magnetic and in-plane electric fields - Chaika, Andrii; Kulynych, Yelizaveta; Oriekhov, Dmytro; Sharapov, Sergei (Physical Review B, 2025)
The density of states and differential entropy per particle are analyzed for Dirac-like electrons in graphene subjected to a perpendicular magnetic field and an in-plane electric field. For comparison, the derived density of states is contrasted with the well-known case of nonrelativistic electrons in crossed magnetic and electric fields. The study considers ballistic electrons and also includes the effect of small impurity scattering. In the latter case, the limit of zero magnetic field and the so-called collapse of Landau levels in graphene are examined analytically. By comparing the results with numerical calculations on graphene ribbons, we demonstrate that the Landau state counting procedure must be modified for Dirac-like electrons, leading to a fields-dependent Landau level degeneracy factor. Additionally, it is shown that peaks in the differential entropy arise from the dispersionless surface mode localized at the zigzag edges of the ribbon.